The Movement of Venezuelans to the Americas and the Caribbean in the 21st Century
XXIX, 363 p.
Keywords: Citizens in the contemporary era are increasingly residing in an age of constant migration, however, not all migratory movements are fully understood as migrants are often excoriated on entry to host countries. It is therefore important to enhance our understanding of migration, especially from nations that were once touted as being all-conquering, powerful, and mighty, as is the case of Venezuela. The Movement of Venezuelans to the Americas and the Caribbean in the 21st Century places singular focus on the migration of Venezuelans into the Americas and smaller nation states of the Caribbean and offers a plethora of ontologies and insights into the phenomenon. This riveting and captivating book is written by experts in a range of disciplines, including, but not limited to, criminology and criminal justice, sociology, policing, national security studies, migration studies, and social work. Instructively, it is the transdisciplinary nature of the work that makes the booklimitless in nature and scope. The book makes a valuable contribution to academe as it plugs a lacuna in the literature on Venezuelan migration in the early 21st Century and enhances our understanding of the phenomenon. Edited by eminent Caribbean scholar, Dr. Wendell C. Wallace, The Movement of Venezuelans to the Americas and the Caribbean in the 21st Century is a must read for anthropologists, criminal justice practitioners, psychologists, political scientists, social workers, migration specialists as well as individuals who are interested in understanding the migration of Venezuelans in the first two decades of the 21st Century.